A review of the animal models of Atherosclerosis - Habibyar, Ahmad Farid; Noori, Abdul Sabor (Journal of Natural Sciences – Kabul University, 2024)
Atherosclerosis is a complex inflammatory disease of the arteries that leads to the cardiac attack and stroke. Atherosclerosis claims thousands of lives each year. The animal models of atherosclerosis increased our knowledge about atherosclerosis and helped us with the discovery of new medicines for this disease. The aim of the present study is to review the role of animal models in the research of drugs for atherosclerosis treatment. This is a library research for which useful literature sources are used. From our findings it can be concluded that the animal models for atherosclerosis include: atherosclerosis induced by cholesterol-rich diet, hereditary hyperlipidemia in rabbits and mice, genetic changes, endothelial function changes in rabbits with atherosclerosis and intimal reactions after endothelial damage. Genetic models are widely used. Through discovering new medicines animal models have brought positive changes in the field of treating this disease and understanding how it progresses.